Are women overrepresented among the poor? An analysis of poverty in ten developing countries - Quisumbing, Agnes R.; Haddad, Lawrence J.; Peña, Christine (International Food Policy Research Institute, 2001)
This paper presents new evidence on the proportion of women in poverty in ten developing countries. It compares poverty measures for males and females and male- and female-headed households, and investigates the sensitivity of these measures to the use of per-capita and per-adult equivalent units and different definitions of the poverty line.